MEDIA PEMBELAJARAN DALAM PERSFEKTIF AL QUR’AN KAJIAN SURAT AN NAHL AYAT 78 - rahimi (Akademika: Jurnal Keagamaan dan Pendidikan, 2022)
Media is something that can produce information and can process it systematically without having to be restated. The media is derived from Latin which means intermediary. This meaning can be said to be a communication tool used to carry information from source to receiver. The position of the learning media by them is that the learning media process is a communication process and it takes place in a system, so the learning media occupies an important position as one of the components of the learning system. Al-Qur'anul Karim is the greatest miracle of Islam and its miracles are always strengthening knowledge, He was sent down by Allah to His Messenger, Muhammad SAW to get people from dark to light and guide them to a straight path. And also whoever reads it becomes a worship for him.